Regulação do meio ambiente de trabalho e a prevenção à violência psicológica profissional - Ramos, Izabel Christina Baptista Queiroz (2024)
This thesis addresses and investigates the various forms and impacts of psychological violence in the workplace and the relationship between self-management of the work environment and the adoption of preventive measures against professional psychological violence as means to enforce the fundamental right to health and promote dignified and decent work. The general objective of the research is to analyze, based on doctrinal, clinical-scientific, and statistical study, and from the international perspective on occupational health and the work environment, the impacts of psychological violence on the individual worker and the work environment, with a focus on the prevention and combat of this type of violence, both from the internal perspective of the workplace and in terms of the role of the Labor Public Prosecutor's Office and legislative activity. The adopted methodology is of a bibliographic and documentary nature, based on the deductive method. In the end, regulatory legal text guidelines for corporate prevention against psychological violence at work are indicated, to fill the still persistent national legal gap.